A note on informality in the labor market - Melanie Khamis (Institute for the Study of Labor (IZA), 2009)
This paper provides a detailed analysis of various dimensions of informality in the Mexican labor market. To understand the nature of informality in terms of regulations and compliance, the legalistic view, and in terms of productivity view of the labor market this paper makes an empirical contribution to the debate in the literature on the concept of informality. Questions related to these various concepts, social security and benefits coverage, contractual information, legal status of migrants, the nature of self-employment and job history information are analyzed in terms of their relationship to each other and are also related to individual and household characteristics. This paper finds a substantial overlap between the various concepts, current legal arrangements of social security coverage or contract and also in the individual's job history. In terms of individual characteristics age, education, martial status and scores in the Raven's test, an ability measure, are significant determinants for the various forms of informality, with some degree of variation across the different categories. Overall, a case is made for further studies of household survey data and the implementation of questions relating to different dimensions of informality and their inter-linkages.
Keywords: J40; O17; 330; Informality; social security; contracts; illegal migration; self-employment; job history; Mexico; Schwarzarbeit; Arbeitsmarkt; Informeller Sektor; Mexiko